Properties of ternary blended cement containing metakaolin and fly ash / Mohd Fadzil Arshad ... [et al.] - Arshad, Mohd Fadzil; Megat Johari, Megat Azmi; Mohd Sidek, Muhd Nurhasri; Mohd Noor, Mazlee (Research Management Institute (RMI), 2008)
This paper presents the results of a laboratory study on the properties of Ternary Blended Cement (TBC) containing blends of ordinary Portland cement (OPC), Metakaolin (MK) and Fly Ash (FA). Analyses on the cementitious properties and engineering concrete properties containing TBC produced have been performed. The resulted was than compared with those of OPC and binary blended cementitious (BBC) systems containing OPC:MK and OPC:FA. In general, the results show that the inclusion of MK and FA in TBC alter the properties and performance of the cement paste and concrete to a certain degree as well as the resulting the TBC could potentially be used in the concrete construction industry.